Jorge Bertheau interview - Grané, Jorge (2017)
Jorge Bertheau built his brick house in Escazú, 35 years ago. He studied Architecture in Mexico and, upon his return, worked in Rafael “Felo” García’s design studio with whom he established a deep friendship. Later, Edgar Brenes joined them and together they initiated of founding the School of Architecture, which had little support from the university authorities. With a scholarship offered by England, Jorge  Bertheau and Felo García went there to learn and understand study programs. Later on Edgar Brenes joined them. Upon his return, in 1971, the School was opened, with the “learning to learn” slogan. The new School had detractors and followers. Among the latter was the figure of Engineer Walter Sagot. Bertheau describes the struggle for the survival of the School as “the heroic  moment”, which later diluted with other people and other ideas. Many teachers approached, in the beginning, with  enthusiasm, to support the mission of the School and thus the first Costa Rican architects graduated with success.